When taxation changes the course of the year: fiscal year adjustments and the German tax reform 2000/2001 - Frank Blasch; Alfons J. Weichenrieder (Center for Economic Studies and ifo Institute (CESifo), 2006)
The paper examines 157 German listed corporations that had the option of changing their fiscal year to achieve a possible tax reduction in connection with the major tax reform of 2000/2001. The tax reduction from a change was larger, the larger the expected profits. However, with costs of changing the fiscal year, not all firms that expect a tax reduction from a change may do so. The paper presents empirical evidence that the propensity to change the fiscal year was significantly related to the amount of expected tax savings. This suggests that the corporate tax reduction - in combination with the special German transitory provisions - induced a deadweight loss: corporations incurred a non-tax cost to avoid a tax cost.
Keywords: H25; 330; Steuerplanung; Steuerreform; Unternehmensbesteuerung; Aktiengesellschaft; Deutschland